Competing inequalities: gender versus race in higher education institutions in the UK. Issue 2 (4th March 2021) - Bhopal, Kalwant; Henderson, Holly
ABSTRACT: This article explores findings from two projects that explore the impacts and institutional experiences of the Athena SWAN (ASC) and Race Equality (REC) Charter Marks in UK universities. The article offers an important, timely and original insight into the ways that these two charter marks are shaping and influencing practice in universities. We argue that in higher education policymaking, there has been a privileging of gender over race in terms of addressing inequalities in higher education. Whilst acknowledging the persistence of inequalities in both groups, the data from our projects highlight a significant risk that gender and race inequalities become conflated in current equalities work. We argue that as a consequence of a logic of efficiency that drives Higher Education Institutions (HEIs) to combine gender and race equalities work, and the privileging within this combination of gender, HEIs can publicly work towards equality and inclusion in general terms, without having to confront uncomfortable and deeply embedded practices that perpetuate White privilege in the academy.